Understanding how Canadian healthcare providers have learned to identify co‐occurring PTSD symptoms and dementia in Veterans. Issue 3 (17th February 2022) - Ritchie, Kim; Cramm, Heidi; Aiken, Alice; Donnelly, Catherine; Goldie, Catherine
Accessible Summary: What is known on the subject?: Little is known about how PTSD and dementia in Veterans is identified by health care providers. What the paper adds to existing knowledge?: Healthcare providers identify those behavioural symptoms experienced by older people living with dementia that represent an unmet need associated with PTSD secondary to military service. Once healthcare providers recognize the presence of symptoms relevant to PTSD, they modify their care approach to include focused/tailored non‐pharmacological care interventions that address environmental and situational variables that reflect military action. What are the implications for practice?: Specialized education and training is needed to improve the identification of PTSD when existent with other co‐occurring neurocognitive conditions such as delirium, dementia and depression. Abstract: Introduction: Co‐occurring PTSD and dementia in Veterans can be difficult to distinguish from dementia‐related responsive behaviours, which may result in inappropriate care management. Improved identification of PTSD and dementia is necessary to inform more appropriate and effective care for Veterans. Aim/Question: The purpose of this study was to understand how Canadian healthcare providers have learned to identify the co‐occurrence of PTSD symptoms in Veterans with dementia. Methods: Eight semi‐structured interviews employing the Critical Incident Technique were conducted with key informant healthcare providers who treat Veterans from across Canada. Framework analysis was used to code, sort and develop themes. Results: Observed differences in Veterans with PTSD and dementia cued healthcare providers to seek our more information, leading to a new understanding of past trauma underlying the symptoms they observed. Healthcare providers then altered their usual care approaches to utilize trust‐based and validation‐oriented strategies resulting in more effective care management. Discussion: Improvement in the identification of co‐occurring PTSD and dementia in Veterans requires specialized education and training for healthcare providers. Implications for Practice: Recognizing the complex needs of older Veterans with co‐occurring PTSD and dementia is necessary for healthcare providers to implement more effective care for this population. Relevance Statement: This paper provides mental health nurses with new understanding of co‐occurring PTSD and dementia in Veterans. With an ageing Veteran population in Canada, mental health nurses need to be knowledgeable about the care for Veteran specific mental health needs.